2010
DOI: 10.1021/jf903336t
|View full text |Cite
|
Sign up to set email alerts
|

Picrocrocin Content and Quality Categories in Different (345) Worldwide Samples of Saffron (Crocus sativus L.)

Abstract: In this paper, 345 saffron samples were analyzed from different countries to study their picrocrocin content using different analytical techniques. The E1cm 1% of 257 nm results from all samples are inflated in comparison by the high-performance liquid chromatography (HPLC) data, because of the interferences with the crocetin ester pool and especially with those with a lower trans/cis relation. A picrocrocin range update is proposed for International Organization for Standardization (ISO) 3632 normative becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 13 publications
4
20
0
6
Order By: Relevance
“…Amin et al [72] indicated that a concentration of 1 mg of safranal attenuated the behavioral symptoms of neuropathic pain. Our data indicate that the saffron produced presented high crocin II content (27.7−38.8 mg 100 g −1 DW), almost in line with the saffron produced in Sardinia (Italy, DOP Zafferano di Sardegna) [73], while also presenting a higher content of gallic acid compared to what was found in Iranian and Greek saffron (2 mg and 1.2 100 g −1 DW) by Karimi et al [69] and Proestos et al [74], respectively. Thus, the saffron obtained could be of particular interest for its elevated antioxidant properties.…”
Section: Amf Modulate Crop Performance and Spice Qualitysupporting
confidence: 81%
“…Amin et al [72] indicated that a concentration of 1 mg of safranal attenuated the behavioral symptoms of neuropathic pain. Our data indicate that the saffron produced presented high crocin II content (27.7−38.8 mg 100 g −1 DW), almost in line with the saffron produced in Sardinia (Italy, DOP Zafferano di Sardegna) [73], while also presenting a higher content of gallic acid compared to what was found in Iranian and Greek saffron (2 mg and 1.2 100 g −1 DW) by Karimi et al [69] and Proestos et al [74], respectively. Thus, the saffron obtained could be of particular interest for its elevated antioxidant properties.…”
Section: Amf Modulate Crop Performance and Spice Qualitysupporting
confidence: 81%
“…Thus, the E 1% 257nm values ranged between 74 to 121 and those for E 1% 440nm between 220 and 351. The absolute contents of the respective metabolites determined by RP‐HPLC‐DAD were in line with published data for saffron from different regions (Sánchez and others , 2009; Del Campo and others ; Kyriakoudi and others ; Garcia‐Rodriguez and others ). The established natural ratio of picrocrocin/crocetin esters content (0.5) was then used for the needs of the sensory analysis.…”
Section: Resultssupporting
confidence: 89%
“…Saffron quality is determined by taste, aroma, and colour evaluation, characteristics that are affected by several factors such as soil, climate, rainfall, harvest time, and finally post‐harvest treatments . Picrocrocin, the glucoside precursor of safranal, contributes to the bitterness and it is responsible for its taste, while safranal, a monoterpene aldehyde formed by hydrolysis of picrocrocin during drying and storage, gives the distinctive aroma in saffron (Supporting Information Figure S1). Drying method is therefore crucial, because it determines to a large extent the final quality of saffron and safranal is also involved in several pharmacological activities, well documented elsewhere…”
Section: Introductionmentioning
confidence: 99%